Analysis of genetic profiling, pathomics signature, and prognostic features of primary lymphoepithelioma‐like carcinoma of the renal pelvis. Issue 20 (2nd September 2022) - Fan, Bo; Huang, Yuanbin; Zhang, Hongshuo; Chen, Tingyu; Tao, Shenghua; Wang, Xiaogang; Wen, Shuang; Wang, Honglong; Lin, Zhe; Liu, Tianqing; Zhang, Hongxian; He, Tao; et al.
Abstract : The genetic features of primary lymphoepithelioma‐like carcinoma (LELC) of the upper urinary tract have not been systematically explored. In this study, tumor mutation profiling was performed using whole‐genome sequencing in two patients with LELC of the renal pelvis. Novel candidate variants relevant to known disease genes were selected using rare‐variant burden analysis. Subsequently, a population‐based study was performed using the Surveillance, Epidemiology, and End Results (SEER), PubMed, MEDLINE, Embase, and Scopus databases to explore clinical features and prognostic risk factors. Immunohistochemical analysis revealed seven positive cytokeratin‐associated markers in tumor cells and five positive lymphocyte‐associated markers in and around the tumor area. Sub‐sequently, we identified KDM6A as the susceptibility gene and LEPR as the driver gene by Sanger sequencing in case 2 of LELC of the renal pelvis. Three mutation sites of the existing targeted drugs were screened: CA9, a therapeutic target for zonisamide; ARVCF, a therapeutic target for bupropion; and PLOD3, a therapeutic target for vitamin C. In a population‐based study, patients with primary LELC of the upper urinary tract had clinical outcomes similar to those of patients with primary upper urinary tract urothelial carcinoma (UUT‐UC) before and after propensity score matching at 1 : 5. Focal subtype was an independent prognostic factor for the overall survival of patients with LELC of the upper urinary tract. The carcinogenesis of primary LELC may be due to different genetic variations, including single‐nucleotide variants, insertion and deletions, structural variations, and repeat regions, which may provide the basis for clinical diagnosis and treatment. The prognosis of LELC in the upper urinary tract is similar to that of UUT‐UC. We suggest that the focal subtype can serve as a prognostic factor for LELC of the upper urinary tract; however, further studies are required to confirm this. Abstract : Here, the genetic, pathological and prognostic features of primary lymphoepithelioma‐like carcinoma (LELC) of the renal pelvis are explored. Mutations in the driver gene LEPR and susceptibility gene KDM6A might be associated with LELC of the renal pelvis. The prognosis of LELC of the upper urinary tract is similar to that of UUT‐UC.